Interrater Agreement between Bedside and Video Raters Using the CPOT-Neuro for Pain Assessment in Critically Ill Patients with a Brain Injury - Vivienne Nguyen; Melissa Richard-Lalonde; Céline Gélinas (MDPI AG, 2024)
This study aimed to examine the interrater agreement of Critical-Care Pain Observation Tool-Neuro (CPOT-Neuro) scores as a newly developed tool for pain assessment in patients with critical illness and brain injury between raters using two methods of rating (bedside versus video) during standard care procedures (i.e., non-invasive blood pressure and turning). The bedside raters were research staff, and the two video raters had different backgrounds (health and non-health disciplines). Raters received standardized 45 min training by the principal investigator. Video recordings of 56 patient participants with a brain injury at different levels of consciousness were included. Interrater agreement was supported with an Intraclass Correlation Coefficient (ICC) > 0.65 for all pairs of raters and for each procedure. Interrater agreement was highest during turning in the conscious group, with ICCs ranging from 0.79 to 0.90. The use of video recordings was challenging for the observation of some behaviors (i.e., tearing, face flushing), which were influenced by factors such as lighting and the angle of the camera. Ventilator alarms were also challenging to distinguish from other sources for the video rater from a non-health discipline. Following standardized training, video technology was useful in achieving an acceptable interrater agreement of CPOT-Neuro scores between bedside and video raters for research purposes.